2013
DOI: 10.1144/sp387.2
|View full text |Cite
|
Sign up to set email alerts
|

Surface-based reservoir modelling for flow simulation

Abstract: We present a surface-based approach to reservoir model construction in which all geological heterogeneity, whether structural, stratigraphic, sedimentological or diagenetic, that impacts on the spatial distribution of petrophysical properties is modelled as one or more discrete volumes bounded by surfaces. The modelled surfaces can be deterministically interpolated between control lines or points, or incorporate a stochastic element where control data are sparse. Models constructed from surfaces are not constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 43 publications
0
30
0
1
Order By: Relevance
“…Although these studies have demonstrated that, under certain displacement conditions, it is important to include clinoforms in models of shallow-marine reservoirs, it is not clear how these models could be applied in the subsurface or at the full-field scale. Other studies have indicated that surfaces should be used to incorporate clinoforms into reservoir models, as surfaces are much less computationally expensive to generate and manipulate than large 3-D geocellular grids Sech et al, 2009;Jackson et al, 2014). These deterministic approaches are appropriate for modeling clinoforms that are tightly constrained by outcrop data but do not allow flexibility in conditioning clinoform geometry and distribution to sparser data sets with a large degree of uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies have demonstrated that, under certain displacement conditions, it is important to include clinoforms in models of shallow-marine reservoirs, it is not clear how these models could be applied in the subsurface or at the full-field scale. Other studies have indicated that surfaces should be used to incorporate clinoforms into reservoir models, as surfaces are much less computationally expensive to generate and manipulate than large 3-D geocellular grids Sech et al, 2009;Jackson et al, 2014). These deterministic approaches are appropriate for modeling clinoforms that are tightly constrained by outcrop data but do not allow flexibility in conditioning clinoform geometry and distribution to sparser data sets with a large degree of uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…At present, virtually all reservoir modelling systems are based on cellular grids that are populated with properties (Denver & Phillips 1990). Gridded models are associated with problems and, while in the future we may be less dependent on such an approach (Jackson et al 2013), at present gridded models are industry standard. Grid design includes layer strategy and grid resolution (including grid cell dimensions and variability), as well as grid cell geometry.…”
Section: Analogue Data In the Reservoir Modelling Workflowmentioning
confidence: 99%
“…Grid design includes layer strategy and grid resolution (including grid cell dimensions and variability), as well as grid cell geometry. The grid design can significantly impact the behaviour of the model (Jackson & Muggeridge 2000;Yoon et al 2001;Jackson et al 2013). Grid design is a key part of the conceptual model, and should reflect the knowledge on the scale and geometry of heterogeneities, in relation to fluid types present, which will impact flow.…”
Section: Analogue Data In the Reservoir Modelling Workflowmentioning
confidence: 99%
See 1 more Smart Citation
“…A surface-based approach to model construction Jackson et al, 2014) was followed, in which surfaces are used to represent both key stratigraphic surfaces and facies boundaries. Surfaces are modeled before the grid is defined, so model geometry is not limited by grid resolution ).…”
Section: Model Constructionmentioning
confidence: 99%